Augmenting Seed Potato Yield Through Nutritional Protocols and Investigating Their Residual effect on Spring Maize: Residual nutritional effects in pototo-maize system - C S Aulakh; A S Sidhu; singh, Amanpreet (Journal of Cereal Research, 2025)
Punjab, contributing over 85% of India’s seed potato demand, faces a paradox of high production area but suboptimal productivity due to imbalanced nutrient management, particularly phosphorus. A field study was conducted over two years (2019–2020) at two sites (Ludhiana and Jalandhar) to evaluate the effect of integrated phosphorus management—using organic amendments (farmyard manure and biofertilizer) and graded phosphorus levels—on the growth, yield, and seed efficiency of potato and its residual impact on subsequent spring maize. Results revealed that farmyard manure (FYM) significantly enhanced dry matter accumulation, tuber bulking rate, and seed tuber yield, with average increases in medium-sized tuber yield by 21–28% and total tuber yield by 16–22% over the unfertilized control. Phosphorus application at 125 kg P₂O₅ ha¹ further improved yield attributes, resulting in 14–19% higher total tuber yield compared to lower P levels. Seed production efficiency was maximized (up to 38.72) under FYM and high phosphorus regimes, indicating improved resource utilization. Notably, the residual phosphorus from potato treatments positively influenced spring maize, with FYM plots showing 8.2–11.5% yield enhancement over the control, highlighting sustained soil fertility benefits. The findings underscore the value of integrating organic and mineral phosphorus sources for sustainable seed potato production while maintaining productivity in succeeding maize crops.